2003
DOI: 10.1046/j.1365-2672.2003.01944.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characterization of competitive exclusion products for use in poultry

Abstract: Aims: Phenotypic and genotypic bacteria identification methods were compared for their efficacy in determining the composition of competitive exclusion (CE) products. Methods and Results: Phenotypic methods used for bacterial identification were fatty acid methyl ester profiles, biochemical assays and carbohydrate utilization profiles. Genotypic methods were MicroSeq16S rRNA sequence analysis and BLAST searches of the GenBank sequence database. Agreement between phenotypic and genotypic methods for identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…It is possible that the L. lactis isolate acquired a vancomycin resistance gene from a vancomycin-resistant Enterococcus sp. that was present in the CE product [8]. In the present study, we hypothesize that the vancomycinresistant L. lactis isolate may have the potential to transfer resistance determinants to a S. aureus strain similar to those that normally transit the human GI tract [9].…”
Section: Introductionmentioning
confidence: 80%
“…It is possible that the L. lactis isolate acquired a vancomycin resistance gene from a vancomycin-resistant Enterococcus sp. that was present in the CE product [8]. In the present study, we hypothesize that the vancomycinresistant L. lactis isolate may have the potential to transfer resistance determinants to a S. aureus strain similar to those that normally transit the human GI tract [9].…”
Section: Introductionmentioning
confidence: 80%
“…Hence, the early administration of 'good' bacteria for competitive exclusion has been proposed as a method to prevent undesirable infections. There are several reports on the capacity of live bacterial cultures (Callaway et al, 2008;Corrier et al, 1998;Nisbet et al,1998;Wagner et al, 2003) and probiotic organisms (Higgins et al, 2007;Higgins et al, 2008;Higgins et al, 2010;Patterson & Burkholder, 2003;Vicente et al, 2008) to reduce the colonization of the gastrointestinal tract of poultry by opportunistic pathogens. The current study showed that the dietary inclusion of Bacillus subtilis enhanced the birds' immunity against Newcastle disease and avian influenza.…”
Section: Assessment Of a Probiotic Containing Bacillus Subtilis On Thmentioning
confidence: 99%
“…belonging to Lancefield groups B and C failed to be identified with the Rapid Strep system (Watts and Yancey, 1994). Therefore, comparison of the 16S rRNA sequences of investigated bacteria has high discriminatory power to resolve closely related species (Wagner et al, 2003). MicroSeq500 16S rRNA sequencing is an excellent commercial identification assay marketed for the rapid and accurate identification of bacterial pathogens (Woo et al, 2009) via sequencing the first 500 base pairs of the 16S rRNA gene.…”
mentioning
confidence: 99%